Gender Differentials of Non-communicable Diseases: A Case Study of Sri Lanka with Special Reference to Cardiovascular Diseases, Diabetes and Cancer - Hansa Andradige; Liwan Liyanage (Athens Journal of Health and Medical Sciences)
Sri Lanka presents higher life expectancy (LE) of 76 years among its citizens which also marks a substantial male-female gap. Considering the country’s deaths, deaths due to non-communicable diseases are on the rise also indicating differences among males and females. The main objective of this study is to explore the gender differentials of non-communicable diseases in Sri Lanka. The study uses secondary data collected from 2010-2015 by the Registrar General’s Department and the Department of Census and Statistics (2015). Arriaga’s decomposition techniques of life expectancy and the calculation of causespecific death rates have been utilised in the main analysis. Decomposition of LE indicates that major contribution is through the indirect effect, which is 3.5 years considering the LE change during 2011-2013. Results reveal that males have a higher number of deaths due to NCDs compared to women. Considering the main three diseases of cancer, cardiovascular and diabetes, prevalence and mortality is relatively higher among males than females in most districts. It is important to identify the gender differentials in the mortality of the most common NCDs in order to support policy planning related to the management of the health and wellbeing of the population.